2007
DOI: 10.1177/1077559506296317
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Are Family Treatment Drug Courts? Outcomes From a Four-Site National Study

Abstract: Family treatment drug courts (FTDCs) are a rapidly expanding program model designed to improve treatment and child welfare outcomes for families involved in child welfare who have substance abuse problems. The present study compares outcomes for 250 FTDC participants to those of similar parents who did not receive FTDC services in four sites. Results show that FTDC parents, compared to comparison parents, entered substance abuse treatment more quickly, stayed in treatment longer, and completed more treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 5 publications
3
99
0
Order By: Relevance
“…Common themes include regular meetings with a designated judge who actively manages the case; a focus on recognizing and rewarding achievements; better coordination of services for families; and a specialized team who works with families to improve such coordination. Overall, the FDTCs have promising findings, suggesting swifter access to drug treatment, higher rates of reunification with parents and no indications of this being associated with subsequent breakdown (Boles et al 2007;Green et al 2007;Worcel et al 2008). One somewhat concerning finding was that Worcel et al (2008) found that for children permanently placed elsewhere, final placement took longer in an FDTC.…”
Section: Introductionmentioning
confidence: 93%
“…Common themes include regular meetings with a designated judge who actively manages the case; a focus on recognizing and rewarding achievements; better coordination of services for families; and a specialized team who works with families to improve such coordination. Overall, the FDTCs have promising findings, suggesting swifter access to drug treatment, higher rates of reunification with parents and no indications of this being associated with subsequent breakdown (Boles et al 2007;Green et al 2007;Worcel et al 2008). One somewhat concerning finding was that Worcel et al (2008) found that for children permanently placed elsewhere, final placement took longer in an FDTC.…”
Section: Introductionmentioning
confidence: 93%
“…Of the two, there is more evidence that FDTCs increase reunification rates; nine studies found an increase in reunification for participants (Ashford, 2004;Boles, Young, Moore, & DiPirro-Beard, 2007;Burrus, Mackin, & Finigan, 2011;Chuang, Moore, Barrett, & Young, 2012;Dakof et al, 2010;Gifford, Eldred, Vernerey, & Sloan, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2009;Green, Rockhill, & Furrer, 2007b;Worcel, Furrer, Green, Burrus, & Finigan, 2008). Several studies found reduced time spent in foster care for children of participants (Bruns, Pullmann, Weathers, Wirschem, & Murphy, 2012;Burrus et al, 2011;Gifford et al, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2007a;Worcel et al, 2008), although one study reported longer stays (Chuang et al, 2012) and another found the effect varied by court (Green et al, 2009). To date, long-term outcomes have not been evaluated.…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%
“…To date, long-term outcomes have not been evaluated. With the exception of one study that found no difference in the probability of a subsequent maltreatment report between FDTC participants and the treatment-as-usual group (Green et al, 2007a), no studies have examined whether children who were reunited with their parents after treatment had better long-term outcomes. Further, it is not known whether parents who enter FDTCs when they are able to maintain custody during treatment are more successful and/or their children have better outcomes.…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%
“…New promising treatment approaches that combine pharmacotherapies and behavioral therapies have emerged (Jonas et al, 2014;Miller, Locastro, Longabaugh, O'Malley, & Zweben, 2005). Evidence supports the use of drug courts as systems for coordinating and judicially supervising treatment for individuals involved with the criminal justice system as a result of problems with alcohol or other drugs (Brown, Allison, & Nieto, 2011) and for families involved in the child welfare system (Green, Furrer, Worcel, Burrus, & Finigan, 2007;Smith, 2003).…”
Section: Demonstrable Progress Toward the Challenge Can Be Made In A mentioning
confidence: 99%